Triangulating ESG Communication Effectiveness: Combining Internal Narratives, Public Perceptions, and Secondary Evidence - Dea Sona Alamanda; Nila Armelia Windasari (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
Environmental, social, and governance (ESG) communication is expected to strengthen legitimacy and trust, yet its effectiveness is rarely assessed by looking at how internal narratives, public perceptions, and formal disclosures line up with each other. This study evaluates ESG communication effectiveness in an Indonesian state-owned enterprise by comparing what the company believes it communicates, what is documented in official channels, and what the public actually perceives. The research uses a descriptive-qualitative case design supported by descriptive survey data and a triangulation method that combines semi-structured interviews with communication and sustainability practitioners, an online survey of 106 internet users, and secondary evidence from sustainability reports, annual reports, and corporate websites. These three evidence streams are organized into a convergence–divergence matrix covering visibility, message clarity, credibility, channel fit, and brand architecture. Results show a clear misalignment: unaided awareness of the company’s ESG initiatives is only 17.0%, message clarity is moderate (2.42/4), and credibility is perceived as fair (3.30/5), despite the presence of assured ESG data and active digital channels. The study concludes that the main weaknesses of current ESG communication lie in salience, clarity, and explicit brand ownership, while channel choice and the availability of proof-points are relative strengths. The findings support prior work on ESG communication gaps and extend it by showing how the use of a white-label ESG campaign brand can unintentionally weaken the link between ESG performance and the corporate brand, thus highlighting the importance of aligning content, channels, and brand architecture in future ESG communication strategies.